Isolation and identification of phenolic compounds from the leaf extract of Cassia alata L. - Duong, Pham Quang; Duyen, Nguyen Thi; Quyen, Phung Ton; Tung, Nguyen Quang; Son, Vu Hong; Hung, Vu Dinh; Quang, Le Dang (Vietnam Journal of Chemistry, 2017)
Cassia alata is one of the most important species of the genus Cassia which is rich in anthraquinones and polyphenols. This plant is used as a medicinal material of which the leaves are known to have laxative and antibiotic properties. In our study, the methanol leaf extract of C. alata showed a significant antibacterial activity against human pathogenic bacteria strains Staphylococcus aureus and Bacillus cereus. The organic layers such as n-hexane, ethyl acetate, and aqueous layers, were prepared by partitioning the methanol extract with n-hexane and ethyl acetate successively.  We successfully isolated and identified the structures of five compounds from C. alata leaves. Their structures were elucidated by MS and NMR spectroscopic methods as well as comparison with literature data. These compounds were determined to be methyl 2,4,6-trihydroxybenzoate (1), kaempferol (2), (-)epiafzelechin (3), kaempferol-3-O-glucoside (4) and kaempferol-3-O-gentiobioside (5). Keywords. Cassia alata L., epiafzelechin, kaempferol, kaempferol-3-O-glucoside, kaempferol-3-O-gentiobioside.